Reforms and infrastructure efficiency in Spain's container ports - Trujillo Castellano, Lourdes (Policy research working paper, 2005)
"Serrano and Trujillo quantify the evolution of technical efficiency in port infrastructure service provision in the major Spanish port authorities involved in container traffic. They also analyze the extent to which port reforms that took place in the 1990s had an impact on the efficiency of the Spanish container ports. Because of the multi-output nature of port activities, the authors have estimated a distance function, which is a novel methodology in the study of the port industry. Their results show that the reforms resulted in significant improvements in technological change, but that technical efficiency has in fact changed little on average. But there is a significant movement of the efficiency within ports over time as a result of these reforms. This paper--a product of the Office of the Vice President, Infrastructure Network--is part of a larger effort in the network to document the impact of regulatory reform"--World Bank web site